A pilot study on treatment of infantile cystinosis with mesenchymal stem cells - Gok, Faysal; Zeybek, Cengiz; Balat, Ayse; Jones, Olcay Y (Journal of Clinical Nephrology, 2019)
Infantile cystinosis is a lysosomal storage disease leading to end stage kidney disease at early ages. There is no effective treatment and patients require long term dialysis or kidney transplant for survival. We present our experience on three affected children who received HLA matched allogeneic stem cell transplant. The protocol used was novel and designed to promote engraftment. The primary endpoint was safety for treatment related mortality or morbidity; All three children survived without serious adverse effects during extended follow up for over 4 years. Although we could not prove engraftment, all three children met secondary end point of sustained target functions over a 6 month follow-up. Further studies are warranted to further evaluate safety and efficacy of MSC treatment for infantile cystinosis.